Descriptive analysis of mycological examination of patients with onychomycosis treated in private practice - John Verrinder Veasey; Flávio Nappi; Clarisse Zaitz; Laura Hitomi Muramatu (Sociedade Brasileira de Dermatologia, 2017)
ABSTRACT This is a retrospective study of 160 patients treated in private practice in São Paulo from March 2003 to March 2015. We analyzed 171 results of direct mycological examinations and fungal cultures from nail scrapings. The agreement between direct mycological examination results and fungal culture was satisfactory, consistent with the literature (kappa 0.603). The main agent identified was Trichophyton rubrum (51%). We observed an isolation rate of non-dermatophyte filamentous fungi superior to the literature (34%). Determining the agent is key to defining the appropriate onychomycosis treatment, and knowing the epidemiology of patients treated in private practice helps the dermatologist who works in this context.